Knowledge driven development : bridging waterfall and agile methodologies - Lal, Manoj Kumar (Cambridge IISc series, 2018)
"The majority of IT projects necessitate the incorporation of domain knowledge into working software. This knowledge needs to be consistently managed across the project's activities and outputs. This book assesses how two well-known software development methodologies - Waterfall and Agile - attempt to meet this challenge. Both approaches exhibit a number of strengths, but also some weaknesses. An alternative model, the Project Knowledge Model (PKM), is put forward. The model scopes the knowledge relevant to the project into a specified number of data points assisting in its digitisation. It establishes a connection between enterprise knowledge and project knowledge for continuous improvement and accelerated project delivery. It can assist existing methodologies in managing knowledge better and has been further developed into a new methodology: Knowledge Driven Development (KDD)"--